Dry season pan evaporation in fallow and irrigated rice fields - Akhand, Md. Nurul Alam; Olesen, Svend Elsnab; Eggers, Helmut; Apichart Anukularmphai; UNDP (Bangkok : Asian Institute of Technology, 1980)
A field experimental program was conducted in Mahasarakam Pumping Irrigation Project, Northeast Thailand, during the dry season of 1980 to determine the variation in pan evaporation and meteorological factors in fallow and irrigated rice fields, and to find the ratio of potential evapotranspiration to pan evaporation. Eight screened class A pans were placed in fallow and irrigated rice fields along transect line of 2. 5 km. Two extra pans were placed outside the transect line to evaluate the effect of screening the pans. The experiment included daily observation of pan evaporation, air temperature, dry and wet bulb temperatures and wind run. Advection resulted in a decrease in evaporation of about 15 percent at a distance of 100 m inside the rice field from the fallow-rice field boundary. Within rice fields evaporation decreased about 8 percent over a distance of 1.4 km. The maximum decrease in evaporation was 29 percent along the transect line. Evaporation increased about 11 percent at a distance of 150 m in fallow field from the tail of a rice field. Average temperature, vapor pressure deficit and wind run between 0800 and 1100 hours decreased upto 2 °c, 7.6 mbar and 0.3 m/s respectively from fallow to rice fields along the transect line. The ratio of potential evapotranspiration to pan evaporation was almost constant for fallow fields. In rice fields the ratio was influenced to some extent by the stages of crop growth, and the average values for the four rice field stations were 0.85, 0.92, 0.93 and 0.90 at recovery, tillering, flowering and ripening stages respectively. The ratio of screened pan evaporation to unscreened pan evaporation was 0.87.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1980
Keywords: Irrigation farming; Evaporation (Meteorology)